Problems the first year students encounter in EFL learning at private universities of Bangladesh: Four private universities in consideration - Md. Mehedi Hassan; MD. Nazmul Haque (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2023)
The English language becomes a key factor in the academic life of first-year FFL learners at the graduation level in Bangladesh as this is the first time when they have to be exposed to English Medium Instruction (EMI). When the first-year FFL learners at private universities try to speak and write in English it becomes a challenge for them. The research intends to find out the first-year FFL learners problems they face at Private Universities in Bangladesh and some suggestions to overcome them. 40 FFL learners from 4 different private universities participated and the mixed method comprising qualitative and quantitative methods is applied in this study. The data has been collected through the research instruments like survey questionnaires and interviews. The study recommends that vocabulary skills, pronunciation, teaching techniques of teachers, syllabus design, motivation, and a proper environment are important factors that should be developed to enhance their communicative competence. And for overcoming these problems they need motivation, to know more words and their use in sentences, and knowledge regarding sentence structures. And also they need an English reading environment inside and outside of their classroom.